2020
DOI: 10.4491/eer.2020.167
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of low density polyethylene-degrading bacteria isolated from soils of waste disposal sites

Abstract: The current study focused on an environment friendly method for degradation of Low Density Polyethylene (LDPE) using bacteria. A total of 36 bacterial strains were isolated from waste disposal sites in which six strains showed potential biodegradation activities. In this study, we reported 2 new strains i.e. Bacillus siamensis and Bacillus wiedmannii for LDPE degradation. The percent weight loss of LDPE films for isolates was; B. siamensis (8.46 ± 0.3%), B. cereus (6.33 ± 0.2%), B. wiedmannii (5.39 ± 0.3%), B.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 41 publications
(63 reference statements)
0
4
0
Order By: Relevance
“…For example, Enterobacter and Pseudomonas exhibited significant biodegradation of plastics, showing up to 15% weight loss in 120 days [74]. Similarly, Maroof et al (2021) also revealed that a new bacterial strain, B. siamensis, showed a degradation ability with a percentage of 8.46% LDPE after 90 d of incubation [75].…”
Section: Discussionmentioning
confidence: 94%
“…For example, Enterobacter and Pseudomonas exhibited significant biodegradation of plastics, showing up to 15% weight loss in 120 days [74]. Similarly, Maroof et al (2021) also revealed that a new bacterial strain, B. siamensis, showed a degradation ability with a percentage of 8.46% LDPE after 90 d of incubation [75].…”
Section: Discussionmentioning
confidence: 94%
“…The amorphous region of LDPE was found disintegrated in the treated sample. Bacillus siamensis and Bacillus wiedmannii decreased the crystallinity percentage of LDPE after 90 days of incubation [46]. The crystallinity of LDPE was decreased by treating with the mixed cultures of Aspergillus sp.…”
Section: Ldpe Analysis Using Xrdmentioning
confidence: 97%
“…HY-71 Polyester-polyurethane 23.95% Kim et al (2022) 8 Acinetobacter pitti Low-density polyethylene (LDPE) 26.80% Montazer et al (2018) 9 Serratia sp. LDPE 40% Nadeem et al (2021) 10 Bacillus siamensis LDPE 8.46% Maroof et al (2021) 11 Bacillus cereus LDPE 6.33% Maroof et al (2021) 12 Bacillus wiedmannii LDPE 5.39% Maroof et al (2021) 13 Proteus mirabilis LDPE 89.72% Akhiqbe et al (2022) 14 Enterobacter sp. Polypropylene 64% Skariyachan et al (2021) 15 Staphylococcus sp.…”
Section: Study Selectionmentioning
confidence: 99%
“…Based on these results, pure cultures of bacteria taken from the environment could adhere to, take over, and break down plastic. Maroof et al (2021) found and described the microorganisms that break down several types of plastic. These microorganisms were Bacillus siamensis , B. cereus , and B. wiedmannii , and they were all found in the soils of waste disposal sites.…”
Section: Environmental Plastic Degradationmentioning
confidence: 99%